2010
DOI: 10.1007/s00204-010-0552-6
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity study of 3-monochloropropane-1, 2-diol (3-MCPD) administered by drinking water to B6C3F1 mice showed no carcinogenic potential

Abstract: 3-Monochloropropane-1, 2-diol (or 3-chloro-1,2-propanediol, 3-MCPD) is a well-known food processing contaminant found in a wide range of foods and ingredients. It has been classified as non-genotoxic carcinogen but its carcinogenic potential in the rodents has been controversial. The carcinogenicity to B6C3F1 mice by drinking water administration was assessed over a period of 104 weeks. Three groups, each comprising 50 male and 50 female mice received 3-MCPD at dosages of 30, 100 or 300 ppm up to Day 100 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
1
14
0
7
Order By: Relevance
“…In a long-term toxicity study Jeong et al (2010) investigated the carcinogenicity of 3-MCPD in B6C3F 1 mice by administration in drinking water over a period of 104 weeks. Three groups, each comprising 50 male and 50 female mice received 3-MCPD at levels of 30, 100 or 300 mg/L up to day 100, and 200 mg/L onwards (4.2, 14.3 and 33.0 mg/kg bw per day for males; 3.7, 12.2, and 31.0 mg/kg bw per day for females).…”
Section: Long-term Toxicity and Carcinogenicitymentioning
confidence: 99%
“…In a long-term toxicity study Jeong et al (2010) investigated the carcinogenicity of 3-MCPD in B6C3F 1 mice by administration in drinking water over a period of 104 weeks. Three groups, each comprising 50 male and 50 female mice received 3-MCPD at levels of 30, 100 or 300 mg/L up to day 100, and 200 mg/L onwards (4.2, 14.3 and 33.0 mg/kg bw per day for males; 3.7, 12.2, and 31.0 mg/kg bw per day for females).…”
Section: Long-term Toxicity and Carcinogenicitymentioning
confidence: 99%
“…These data provide support to the premise that these carcinogenic effects are not confined to a specific rat strain. In contrast, no evidence has been found for carcinogenic potential of 3‐MCPD in mice (B6C3F1) after administration in drinking water for 104 weeks 11. Underlying mechanisms that may explain this species specific toxicity have not been elucidated yet.…”
Section: ‐Mcpd(esters): Toxicology and Research Needsmentioning
confidence: 99%
“…It is further oxidized to yield oxalic acid, CO 2 , and chloride. The mechanism of nephrotoxicity of 3‐MCPD has been suggested to be associated with inhibition of glycolysis by metabolites of the β‐chlorolactate pathway 9, 11. In addition, the accumulation of oxalic acid in the kidney also might contribute to chronic progressive nephropathy and subsequent stimulation of renal tubule hyperplasia 11.…”
Section: ‐Mcpd(esters): Toxicology and Research Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeong and others () conducted a carcinogenicity study on 3‐MCPD administered in drinking water to B6C3F1 mice and showed no carcinogenic potential. Their investigation lasted 104 wk, with 3‐MCPD concentrations of 0, 30, 100, and 300/200 ppm.…”
Section: Carcinogenicity Study In Micementioning
confidence: 99%